Regression of Bilateral Peripapillary Choroidal Neovascularization Associated with Idiopathic Intracranial Hypertension after Systemic Acetazolamide Treatment - Omer Trivizki; Liang Wang; Prashanth Iyer; Yingying Shi; Philip J. Rosenfeld; David Rabinovitch; Justin Townsend (Case Reports in Ophthalmology, 2022)
A rare occurrence of bilateral peripapillary choroidal neovascularization (CNV) in an 18-year-old idiopathic intracranial hypertension (IIH) patient regressed with systemic acetazolamide treatment alone. Multimodal imaging was done, including OCT angiography (OCTA), which showed CNV. No injections were given even though she had macular fluid in her left eye. Nonetheless, the subretinal fluid resolved, and visual acuity improved. This report shows that CNV secondary to IIH can be managed with systemic therapy alone. Moreover, we showed for the first time the ability to diagnose IIH-associated CNV using OCTA.